ATHERICIDOS NEOTROPICALES. II. REVISION DEL GENERO DASYOMMA MACQUART 1840 (DIPTERA: ATHERICIDAE) - Coscaron, Sixto; Coscaron, María Del Carmen (Acta Entomológica Chilena, 2022)
The revisión of Dasyomma Macquart, 1840 from the Neotropical Región is performed. Dasyomma (Dasyomma) coeruleum Macquart, D. (D.) croceicornis (Bigot), D. (D.). trivittatum Malloch, D. (D.) poecilogaster (Philippi), D. (D.) vittatum Malloch, D. (Dasyommina) atratulum Malloch, D. (Dasyommina) humerale Malloch, D. ( Trichopalpomya) basale Malloch, D. (T.) atribasis Malloch, D. (T.) immaculatum Malloch, D. (71) cinerascens (Philippi), D. (71) univittatum Malloch are redescribed. The following new species D. (D.) wirthi, D. (D.) gonzalezi, D. (71) trianguliferous, D. (71) malleco and D. (71). chapelco are described, and Dasyomma coeruleum var impressifrons Malloch [= D. coeruleum (Macquart) new syn.] and Dasyomma (D.) atritarsis Malloch [= D. (71) basale (Malloch) new syn.] are synonymized. A genus diagnosis, a key for the species and the geographical distribution are included.